Productivity, stand dynamics and the selection effect in a mixed willow clone short rotation coppice plantation. (April 2016) - Dillen, Mathias; Vanhellemont, Margot; Verdonckt, Pieter; Maes, Wouter H.; Steppe, Kathy; Verheyen, Kris
Abstract: Short Rotation Coppice (SRC) is a promising method of biomass production for energy purposes, but there have been concerns about the low diversity of these stands, including the risk for pest outbreaks. Mixing different clones has been advised as a way to tackle this problem and improve yields through positive diversity effects. Recent research into the relationship between biodiversity and ecosystem functioning supports these recommendations, but also raises worries about mechanisms that may confound results, such as a selection effect due to dominant clones outcompeting weaker ones. However, the few available studies on diversity effects in SRC plantations did not allow the disentangling of the mechanisms at play. We used data from an experimental SRC site, which incorporated three Swedish Salix clones in a row-based mixing design. Productivity was expected to be greater in mixtures and we attempted to elucidate whether this was due to a complementarity or a selection effect. We found that complementarity effects were generally larger than selection effects, yet the total diversity effect on yield was not significant. Leaf surface temperature measurements indicated that drought stress was unlikely to be the factor underlying this distorted diversity productivity relationship. We also found that a less-productive clone (Gudrun) had a different stem biomass distribution when in monoculture, which may have repercussions for the quality of the harvested product and points at a so far less recognized potential benefit of mixing. Highlights: Productivity was assessed in a clonally mixed SRC plantation. We found indications of a positive diversity effect, nevertheless obscured by large yield variability. The complementarity effect seemed more important than the selection effect. Mixing clones altered biomass distribution among stools through compensatory growth.